Pengembangan Bahan Ajar IPA SD Bermuatan Pendidikan Karakter Berbasis Tradisi Lisan Bali - I Made Maduriana; Ni Putu Seniwati (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
AbstractThe Indonesian government has implemented 2013 curriculum focusing on character education. Due to the lacking of textbooks on characted education, it is important to write a draft of natural science textbook on the basis of Balinese oral tradition for elementary school grade 4. The purposes of this study are to create a natural science subject for elementary school and to make a model of cultural and character education on the basis of integrated oral tradition. In relation tho these, this paper will discuss two issues: firstly, what kinds of oral traditions that contain of character education to be developed as natural science material for elementery school grade 4; second, to find out whether or not the draft of textbook will be sufficient for texbook. To solve these problems, literature reviews from eigh libraries in Bali have bee done. Besides, we have carried out a fieldwork, indepth interview as well as focus group discussion. The evaluation of the texbook draft has been performed by teachers of elementery school grade 4. The result is that there are many oral tradition in Bali that could be integrated into natural science material. The texbook draft is qualified for an alternate texbook.